CHARACTERIZATION OF DIET, PHYSICAL ACTIVITY LEVEL AND NUTRITIONAL STATUS OF ADOLESCENTS. (Fiep Bulletin - online, 2015)
Objectives:  to identify factors of nutritional status, physical activity and food related behavior in adolescents. Methods: 297 adolescents of both genders, have been evaluated considering: - physical activity level, using IPAQ; - weight and height, from which BMI were calculated and classified in accordance with WHO; - sistolic and diastolic blood pressure, compared with NHANES III; -24-hour food-recall calculated from energy, macronutrients, iron and calcium. Food also had been evaluated from semi-quantitative and qualitative parameters, in comparison with the Food Pyramid applied the Brazilian population. Results: although the adolescents, in the average, had been considered at normality for the BMI and the blood pressure, an expressive percentual of overweight and obesity was observed Some significant correlations point out to risk factors with respect to development of obesity and chronic diseases:  irregular meals schedules, low micronutrients consumption, and great consumption of sugars and fats. Conclusions: didactic strategies related with nutritional and physical education are recommended.
Keywords: adolescents; diet; obesity.